(-2p-8)/4=6

Simple and best practice solution for (-2p-8)/4=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-2p-8)/4=6 equation:



(-2p-8)/4=6
We move all terms to the left:
(-2p-8)/4-(6)=0
We multiply all the terms by the denominator
(-2p-8)-6*4=0
We add all the numbers together, and all the variables
(-2p-8)-24=0
We get rid of parentheses
-2p-8-24=0
We add all the numbers together, and all the variables
-2p-32=0
We move all terms containing p to the left, all other terms to the right
-2p=32
p=32/-2
p=-16

See similar equations:

| 4x-16=12-5x | | |3x-4|=20 | | v/4+5=17 | | -11r+11(6r+4)=55+10r | | -6x-2x=40 | | 3(w+2)-7w=34 | | 4(x-5)-5=6x=33 | | n^2=14+5n | | 6(x+1)+5=13-2(1-3x) | | 2(2b-1)=15 | | C(x)=0.85x+8 | | w=3/8=1/4 | | 4t+2+5t-8t=3+6 | | 18x+25=24x+13 | | 60+132d-36=-d+7 | | X=525-(63-5x) | | 4t+2+5t-8t=0 | | (5x+9)=(3x+5) | | 0=-16x^2+36x-20 | | 4x^2-16x^2+16=0 | | (5x+10)=(8x-14) | | 5(n+6)+20=20 | | 5y+7=4y+10 | | (5x+9)(3x+5)=0 | | x/8=0.3 | | 165=58-y | | 5x+65=95 | | 9x-13=4x-2 | | 23b^2+85b+26=-4-2b^2 | | 3.26c=8 | | 3g=6+4g | | 20+312n=30+234n |

Equations solver categories